Joint low‐complexity equalization and CFO estimation and compensation for UWA‐OFDM communication systems - Ramadan, Khaled; Ramadan, Khalil F.; Fiky, Ahmed S.; Alam, Hasna; Dessouky, Moawad I.; Abd El‐Samie, Fathi E. (International journal of communication systems, 2020)
Summary Frequency synchronization has a great importance in preserving the performance of the underwater acoustic (UWA) orthogonal frequency division multiplexing (OFDM) systems. The carrier frequency offset (CFO) estimation can be blind or data‐aided. In this paper, the Zadoff‐Chu (ZC) sequences are used for OFDM synchronization in UWA communications, and they are compared with different data‐aided algorithms. We propose a low‐complexity algorithm for CFO estimation based on ZC sequences. Also, a joint equalization and CFO compensation scheme for UWA‐OFDM communication systems is presented. Simulation results demonstrate that the proposed CFO estimation algorithm allows estimation of the CFO accurately with a simple implementation in comparison with the traditional schemes. Also, the performance of the UWA‐OFDM system can be preserved in the presence of frequency offsets. In this paper, we present a low‐complexity estimation algorithm for carrier frequency offset (CFO) based on the Zadoff‐Chu (ZC) sequences for underwater acoustic (UWA) orthogonal frequency division multiplexing (OFDM) communication systems. The proposed estimation algorithm is compared with other different data‐aided algorithms. Simulation results show that the proposed estimation algorithm provides a wider estimation range than the other range. The performance of the proposed algorithm begins to degrade if the standard deviation of the errors in the channel estimation satisfies the condition σch > 0.1.